Density and management of estuarine crocodile in Samarahan river basin, Sarawak, Malaysian Borneo - Ruhana, Hassan; Mohd Izwan Zulaini, Abdul Gani; Mohammad Azuwan, Hassan; Azroei, DeneL (Prince of Songkla University, Thailand, 2023)
Estuarine crocodile, Crocodylus porosus is the most common crocodile found in Sarawak, Malaysia. Despite its importance in ecological services, socio-economy and cultural belief, crocodiles are still considered pests due to frequent human crocodile conflicts (HCC) resulting in either injuries or death. This study determined the density of crocodiles in three selected rivers within Samarahan River Basin (SRB) of Sarawak, using a standard night spotting technique over a three-year period (2019-2021). The average density of crocodiles in SRB is showing an increasing trend, although there is active removal of the animals from the rivers either by commercial hunting or by relocation of certain individuals as immediate response to HCC. This paper also describes conservation initiatives carried out in SRB aiming to use crocodile as a resource in bioeconomy, which supports the United Nations Sustainable Development Goals.